Status and factors related to hemoglobin concentration of people with vs. without disability—using nationwide claims check-up database - Lee, Seyune; Jung, Young-Il; Yoon, Hyejung; Jung, Se-Youn; Jeon, Boyoung; Oh, In-Hwan; Jeong, Su Jin (Frontiers in Nutrition, 2025)
BackgroundBlood hemoglobin level is a key indicator of organ function and health status throughout the life course. As hemoglobin-related health problems are gaining attention, many studies on factors related to hemoglobin concentration are being conducted, yet few researches have been conducted targeting persons with disabilities. Furthermore, researches that consider the association between blood hemoglobin and the regional level health welfare resources are rare. This study aimed to explore the factors related to blood hemoglobin concentration among people with and without disability, and to contribute to the development of future nutritional policies and projects for persons with disabilities.MethodsA health insurance claims database with check-ups provided by the National Health Insurance Services (NHIS) was used. One-to-three propensity score matching was conducted between participants with and without disabilities. In addition to the individual clinical and health behavioral aspects based on the claims data, regional-level data of healthcare and social welfare resources was also collected, and multi-level analysis was conducted to identify factors associated with low blood hemoglobin level.ResultsA total of 1,697 participants with disability and 5,091 without disabilities were yielded. Disability was significantly associated with lower hemoglobin level, even after propensity score matching. Sex, BMI, health behaviors, and clinical indicators were significantly associated with the blood hemoglobin level. Furthermore, region-level welfare budget was a significant factor among persons with disability.ConclusionOur findings confirmed the significant association between disability and lower hemoglobin level. Regional health and welfare resources, as well as individual characteristics should be considered in implementation of further nutrition and health policies for persons with disabilities. Further studies are needed to understand of health outcomes of low hemoglobin level.